2011
DOI: 10.1002/jcc.21955
|View full text |Cite
|
Sign up to set email alerts
|

Verification of DFT‐predicted hydrogen storage capacity of VC3H3 complex using molecular dynamics simulations

Abstract: Density functional theory (DFT) and Fourth-order Möller-Plesset (MP4) perturbation theory calculations are performed to examine the possibility of hydrogen storage in V-capped VC(3)H(3) complex. Stability of bare and H(2) molecules adsorbed V-capped VC(3)H(3) complex is verified using DFT and MP4 method. Thermo-chemistry calculations are carried out to estimate the Gibbs free corrected averaged H(2) adsorption energy which reveals whether H(2) adsorption on V-capped VC(3)H(3) complex is energetically favorable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The energy trend for the H 2 adsorption on organometallic complex is in good agreement with that observed earlier. [28][29][30][31] It is worthy to note that Van der Waal interaction is included in MP2, and not to be expected in the DFT method. Table 1 does not play much of a role in the adsorption of H 2 on both Ti 2 -C 2 H 4 and Ti 2 -C 2 H 4 + complex which is the same when compared to that observed in previous work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy trend for the H 2 adsorption on organometallic complex is in good agreement with that observed earlier. [28][29][30][31] It is worthy to note that Van der Waal interaction is included in MP2, and not to be expected in the DFT method. Table 1 does not play much of a role in the adsorption of H 2 on both Ti 2 -C 2 H 4 and Ti 2 -C 2 H 4 + complex which is the same when compared to that observed in previous work.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship is in agreement with the earlier results. [28][29][30][31] Natural population analysis shows that the total of about one electron is transferred from each Ti atom to the C 2 H 4 substrate in Ti 2 -C 2 H 4 complex whereas total of about two electrons from each Ti atom to C 2 H 4 + template in Ti 2 -C 2 H 4 + complex, using PBEPBE level of theory. Thus, enhancement in H 2 uptake of Ti 2 -C 2 H 4 complex upon ionization can be observed due to more valence electron transfer from Ti atoms to charged substrate and increase in the metal bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…Jonca et al have used organometallic route for synthesis of ZnO nanoparticles for CO, C 3 H 8 , and NH 3 gas sensing . Organometallic complexes are also used for hydrogen storage …”
Section: Introductionmentioning
confidence: 99%
“…[31] Organometallic complexes are also used for hydrogen storage. [32][33][34][35][36][37] Int J Quantum Chem. 2018;118:e25623.…”
mentioning
confidence: 99%
“…Given the C = C bond is a derivative of C 60 , Durgun [11,12] predicted the hydrogen storage capacities of transition-metal-ethylene complexes and shown that Ti 2 -C 2 H 4 absorbed up to ten hydrogen molecules with the average binding energy of 0.45 eV/H 2 . Under this guidance, numerous studies on hydrogen uptake capacities of organometallic compounds (TM-C 2 H 4 [13][14][15][16][17][18][19] and TM-C n H n , TM stands for first transition metals; n refers to 1 [20], 2 [21][22][23][24], 3 [25][26][27], 4 [28][29][30], 5 [13,[28][29][30][31], 6 [29,32,33], 8 [30]) were carried out theoretically to search for ideal hydrogen storage media. On the experimental side, possibilities of storing hydrogen on Ti-C 2 H 4 complex (12 wt%) [34,35] and Ti-C 6 H 6 complex (6 wt%) [36] have been obtained, respectively.…”
Section: Introductionmentioning
confidence: 99%